Low pneumoperitoneum pressure facilitates postoperative pain relief and gastrointestinal function recovery in laparoscopic gastrointestinal surgery: a systematic review and meta-analysis - Lu, Kai; Peng, Xuefeng; Lan, Ke; Zhang, Faqiang; Cheng, Yong; Yang, Hua (Frontiers in Oncology, 2025)
ObjectiveThe potential benefits of low pneumoperitoneum pressure (LPP) in laparoscopic gastrointestinal surgery, particularly gastric procedures, remain insufficiently investigated. This meta-analysis aims to systematically evaluate the advantages of LPP in laparoscopic gastrointestinal surgery compared to standard pneumoperitoneum pressure (SPP).MethodsA comprehensive literature search was conducted in Embase, Web of Science, PubMed, and Cochrane Library databases from inception to April 10, 2025. Studies comparing LPP with SPP in laparoscopic gastrointestinal surgery, including both randomized controlled trials (RCTs) and observational studies, were systematically reviewed. Data were analyzed using RevMan 5.3 software, with primary outcomes including postoperative pain at rest, pain in post-anesthesia care unit (PACU), and activity-related pain.ResultsTwelve studies were included in the meta-analysis. Compared with SPP, LPP significantly reduced postoperative pain at rest (SMD = -0.40, 95% CI: -0.68 to -0.12, P = 0.005) and pain in PACU (SMD = -1.06, 95% CI: -1.65 to -0.47, P = 0.0004). Additionally, LPP was associated with faster recovery of gastrointestinal function (SMD = -0.27, 95% CI: -0.50 to -0.05, P = 0.02). However, no significant differences were observed between the two groups in terms of activity-related pain, operative time, intraoperative blood loss, surgical field visibility, length of hospital stay, anastomotic leakage, or postoperative complications. Notably, LPP was more frequently associated with intraoperative adjustments to pneumoperitoneum pressure (OR = 4.01, 95% CI: 2.48 to 6.50, P < 0.00001).ConclusionsIn laparoscopic gastrointestinal surgery, LPP provides clinically relevant benefits by reducing postoperative pain at rest and in PACU, as well as accelerating gastrointestinal recovery. However, surgeons should be aware of the potential need for more frequent intraoperative adjustments to pneumoperitoneum pressure when using LPP.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/search, identifier CRD420251037390.